2021
DOI: 10.18178/ijiet.2021.11.1.1481
|View full text |Cite
|
Sign up to set email alerts
|

Towards a Technology-Enhanced Blended Approach for Teaching Arabic for Shari’ah Purposes (ASP) in the Light of the South African National Qualifications Framework

Abstract: The study investigates the use of a blended learning approach for teaching Arabic as a foreign language at a South African Islamic college in the light of the South African National Qualifications Framework level descriptors and their critical cross-field outcomes. In particular, the approach has been used for teaching a Ḥadīth Module in an undergraduate BA programme during the second semester of the academic year 2018-2019 at the International Peace College South Africa (IPSA). The college adopts a content a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…The results also revealed that these educational methods are not available in some colleges in some states, as more than 30 percent of the study participants did not agree with the availability of these educational methods in their colleges, even though they are among the educational techniques mentioned in the Arabic language teaching curriculum of the National Council of Colleges of Education curriculum in Nigeria. These results are consistent with the studies Asmawati et al (2020); Folorunsho (2015); Mohammed et al (2021), which indicated the weak government interest in colleges of Arabic language and Islamic studies, the weak level of professors and lecturers in using educational methods and modern technologies in teaching the Arabic language, and the need for infrastructure such as buildings and equipped classrooms. Using modern technologies and appropriate frameworks for development enhances the effectiveness of these methods in teaching the Arabic language.…”
Section: Discussionsupporting
confidence: 89%
“…The results also revealed that these educational methods are not available in some colleges in some states, as more than 30 percent of the study participants did not agree with the availability of these educational methods in their colleges, even though they are among the educational techniques mentioned in the Arabic language teaching curriculum of the National Council of Colleges of Education curriculum in Nigeria. These results are consistent with the studies Asmawati et al (2020); Folorunsho (2015); Mohammed et al (2021), which indicated the weak government interest in colleges of Arabic language and Islamic studies, the weak level of professors and lecturers in using educational methods and modern technologies in teaching the Arabic language, and the need for infrastructure such as buildings and equipped classrooms. Using modern technologies and appropriate frameworks for development enhances the effectiveness of these methods in teaching the Arabic language.…”
Section: Discussionsupporting
confidence: 89%
“…Hence, this study differs from the previous ones in several aspects. Firstly, it is an extension of other empirical studies that attempted to integrate technology in the teaching of Arabic as a foreign language (Mohammed, 2018;Mohammed, Assam and Saidi, 2020;Mohammed, Al-Sowaidi and Banda, 2021). Unlike other studies, the present study aims to design course content for the teaching of speaking and listening skills which have been described as highly demanding, complicated and multi-faceted (Asakereh and Dehghannezhad, 2015;Walker, 2014).…”
Section: Literature Reviewmentioning
confidence: 99%
“…e design applied the six phases of the ASSURE model. ese phases are analyze the students; state the objectives of the course; select methods, media, and materials; utilize media and materials; require student participation; and evaluate and revise [18]. e e-learning industry has created a wealth of software that makes the design of blended and fully online courses easy and appealing.…”
Section: Literature Reviewmentioning
confidence: 99%